A SURVEY OF LITERATURE ON THE DEVELOPMENT OF GREEN FINANCE AND GREEN BANKING - FĂT CODRUȚA MARIA; FĂRCAȘ IOANA GEORGIANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2024)
The continuous environmental degradation confronts the finance world with a new challenge, namely financing green projects. Therefore, it is relevant to analyze the current literature stand in terms of the development of these financial products, as well as the possible determinants, and effects of these on the banking sector. Our survey of literature presents that most of the previous empirical studies concentrate on the willingness of the financial sector to diminish the environmental impact of financial products, and the costs associated with the implementation of such products. Nevertheless, a high number of studies show the significant role of central banks’ policies related to financial institutions’ activities, especially in green lending. However, a lack of literature that may persist is correlated with the positive determinants of green finance tools that might increase the effectiveness of these financial products to significantly diminish the climate risk